3x-5(x-4)=-9+5-6

Simple and best practice solution for 3x-5(x-4)=-9+5-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-5(x-4)=-9+5-6 equation:


Simplifying
3x + -5(x + -4) = -9 + 5 + -6

Reorder the terms:
3x + -5(-4 + x) = -9 + 5 + -6
3x + (-4 * -5 + x * -5) = -9 + 5 + -6
3x + (20 + -5x) = -9 + 5 + -6

Reorder the terms:
20 + 3x + -5x = -9 + 5 + -6

Combine like terms: 3x + -5x = -2x
20 + -2x = -9 + 5 + -6

Combine like terms: -9 + 5 = -4
20 + -2x = -4 + -6

Combine like terms: -4 + -6 = -10
20 + -2x = -10

Solving
20 + -2x = -10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + -20 + -2x = -10 + -20

Combine like terms: 20 + -20 = 0
0 + -2x = -10 + -20
-2x = -10 + -20

Combine like terms: -10 + -20 = -30
-2x = -30

Divide each side by '-2'.
x = 15

Simplifying
x = 15

See similar equations:

| 3x-12=2x+9 | | 5(3p-7)+25=35 | | 22=4x+2(2x-9) | | -7+2x=7+4x | | (t+10)+(t+20)+t=360 | | -7=5v+8 | | x+31=x | | 5x-5=4x+17 | | -38=-3+5w | | 21=2x+7 | | 2.4-x=x-5.6 | | 57=3w | | 6.8a+13=74.2 | | 21x^3-7x=0 | | 6x-51=13-2x | | 17x-6=11x-18 | | x=3600+x*.945 | | -8x-1=79 | | 4x+5-2x=3+x-12 | | 18-3(8x+4)=-6(4x-1) | | -7-8m=145 | | 1+32=-5(7x-7) | | -0.813+x=-1.096 | | (3x-4y)(7x-4y)= | | x+31=90 | | 4x+7(3x-13)=184 | | 19-3n=8(6n-8) | | 2x+2(3x+8)=-56 | | 4x+14=3x-1 | | x(x-3)+4x-3=8x+x(x+3) | | 2x^3-3x-2=0 | | x+31+x=5x-22 |

Equations solver categories